(untitled) (Research, Society and Development, 2022)
This paper conducts an analysis of the Municipal Education Plan - PME with a focus on what concerns the perspective of special and inclusive education in its Goal 4 of the PME of the municipality of Presidente Figueiredo-PF, better known as the "Land of Waterfalls" located in the Metropolitan Region of Manaus in the State of Amazonas in northern Brazil. With the help of bibliographic and documentary research techniques with a qualitative approach, we conducted an analysis of the strategies outlined in the PME-PF to meet the target audience of special education in their education network, more specifically a discussion of schools in settlement areas. As a result, we observed that of the 18 strategies of Target 4 of the PME-PF, only strategies 4.1 - which refers to the enrolment of special education; 4.3 - which deals with the implementation of multifunctional resource rooms; strategy 4.4 - which provides for the guarantee of specialised educational care through multifunctional resource rooms; and strategy 4.16 - referring to continuing training for education professionals, stand out because they were implemented in the last five years. However, much remains to be done when it comes to an inclusive education perspective. Therefore, even if the paths point to a discontinuity in the educational system, the intention is to move forward believing in a future in which the inclusive school is based on the principles of the 1988 Federal Constitution of equal conditions and permanence in school described in Article 206, paragraph I, as well as the perspective of human rights.